Lexical-Semantic and Linguopoetic Features of Repeated Units in the “Kholdor Khan” Epic - Zuhra Yuldasheva (International Journal on Integrated Education, 2022)
The epic “Kholdor Khan” belonging to the “Gorogli” series is distinguished not only by the uniqueness of the series of events, but also by the uniqueness of its linguistic structure. The artistic-aesthetic manifestations of repeated forms used in the epic are especially noteworthy. Repeated forms are widely used to ensure the content and intonation integrity of the epic. Repetitions in the literary text are always considered as a means of forming the text, as a unit that increases the expressiveness of the expression and creates the completeness of the tone. In the article, the linguopoetic features of repeated units widely used in the epic “Kholdorkhan” are written.